Immobilization of anti-17 beta estradiol antibody on optical fiber surface - Lee, May Ying (2015)
Antibody immobilization onto solid surface has been researched and studied exclusively for biosensor developments and immunoassay applications. In the project, two types of immobilization methods: physical and chemical adsorptions were carried out on optical fiber surface to study the immobilization level measured by Optical Spectrum Analyzer (OSA). The chemical adsorption using the crosslinker, glutaraldehyde (GTA) which allows stronger strength of binding between anti-17 beta estradiol antibody and optical fiber surfaces, showed significantly high antibody immobilization level compared to physical adsorption. The weaker bond of attraction, van der Waals force is one of the limitations of the antibody immobilization by physical adsorption. The chemical reactions between the hydroxyl groups (-OH) on optical fiber surfaces and the silane chemical, 3-aminopropyl-triethoxysilane (APTES) before antibody immobilization were also studied. APTES was useful to modify the surface of optical fiber by chemical reaction to provide binding sites for GTA to activate the surface. Amino groups (-NH2) of antibody could eventually bind with the aldehyde groups (-CHO) of GTA to form amide bond which is a stronger linkage. In addition, the coating of GTA on optical fiber surface was also evaluated by trinocular microscope to investigate the differences between the bare optical fiber and GTA activated optical fiber.